EFFICACY OF DIFFERENT PROTEIN LEVELS ON GROWTH, IMMUNITY AND MEAT QUALITY OF NILE TILAPIA (Oreochromis niloticus) UNDER ZERO EXCHANGE HETEROTROPHIC CULTURE - Irsa Arshad; Abdul Mateen; Sajid Abdullah; Muhamad Sajid Aqeel Ahmad (Journal of Animal and Plant Sciences, 2026)
Biofloc treatment is an eco-friendly and affordable technology which has been adopted over the last three decades to improve aquaculture sustainability. In this study, fingerlings were randomly distributed into different aquariums and fed diets with varying protein levels (15, 20, 25 and 30%). This study investigated the effect of different crude protein (CP) levels on growth, immunity and meat quality of Nile Tilapia (Oreochromis niloticus) under zero exchange heterotrophic culture conditions. Results showed that fish fed 25 and 30% protein diets had the highest growth rate, feed efficiency and protein efficiency ratio. Weigh gain (WG) and specific growth rate (SGR) significantly increase in fish fed 25 and 30 % CP levels (p<0.05). Proximate analysis showed that the fish fed 25 and 30% CP had the highest protein content, lowest lipid content and improved fatty acid profile. Additionally, fish fed 30% protein had the lowest mortality rate and highest survival rate. Immune parameters (WBCs, plasma parameters, lysozyme and antioxidants enzymes activity) were significantly enhanced in fish fed 25 and 30% CP (p<0.05). The best growth performance was obtained when the fish fed on the 25 and 30% CP in diet and can be used as sustainable production of fish under zero exchange heterotrophic culture system.
Keywords: Biofloc; Dietary protein; Heterotrophic culture; Nile Tilapia; Nutrition